Use of Residues from the Processing of Passiflora Edulis «Passion Fruit» Juice for Human Consumption - López Ráez, Luz Eufemia (2021)
The objective was to review the bibliography about the use of residues from the processing of passion fruit juice. Due 96% of the national production of this fruit is destined to the export of juice, where 62% is peel, which is rich in dietary fiber, pectin, among other components; that can be used for the production of by-products, considering that the availability of raw materials and accessibility to food for human consumption is one of the crucial problems facing humanity, understanding that the environmental imbalance was caused by anthropogenic action derived from exploitation and profitability of resources without foreseeing their sustainability for future generations. Given the cost of the experimental tests generated by the design and elaboration of products, this investigation is developed to identify the alternatives of use of the residuals of the raw material, and in a next stage to evaluate their potential to elaborate additional products to the conventional known as by-products. The Scopus and Science Direct databases were used for the systematic review of publications from 2014 to 2020.